Evaluasi Sistem Informasi Pengupahan PT. Tempu Rejo Menggunakan COBIT 5 Domain DSS - Sianipar, Yohana Teresa; Widiyanti, Novi Wulandari; Agustini, Aisa Tri (IAIN Kudus, 2018)
PT. Tempu Rejo is one of the companies in Jember which is engaged in tobacco processing to produce cigarette. PT. Tempu Rejo applying information technology in the daily operation included in its payment information system, such as biometric identifier as a tool of absence and using applications that support payment in the company. In a company that has applied IT in its operation including payment information system should be evaluated. Evaluation is needed in order to make improvements to the company's payment information system. In this research, the information technology governance standard used is COBIT 5 domain Deliver, Service, and Support (DSS), especially DSS01, DSS03, and DSS05. This research used a qualitative approach by using the method of interviewing and observation as data collection techniques. The result of this research shows that Capability Level of DSS01, DSS03, and DSS05 process are at level 3 (established process). Recommendations are to conduct periodic evaluations to improve performance and create a complete Standard Operational Procedure (SOP) related to the company's payment information system.